Inequality and Urban Density: Socio-economic Drivers of Uneven Densification in Cape Town. (March 2021) - Scheba, Andreas; Turok, Ivan; Visagie, Justin
Global policies promote urban compaction to achieve sustainable development. This article highlights the limits of analysing densification at the city scale and advocates for a more granular approach. The case study of Cape Town shows how overall consolidation has been mainly driven by poor households crowding into already dense neighbourhoods on the urban periphery. This has aggravated historic segregation and intensified urban management challenges. Meanwhile, formal private sector driven densification strengthens the social and economic vibrancy of affluent neighbourhoods. This article argues that uneven residential patterns reflect deep-seated social inequalities that are amplified through labour and property markets. Satellite data also illustrates how Cape Town's built-up area has changed between 1998 and 2019. Based on geo-spatial analyses, the article suggests that taking these drivers seriously is crucial to promoting a denser and more equitable urban form. Aligning housing policies with spatial transformation and economic development objectives offer possibilities for change.